The dual pillars of academic excellence: Transformational leadership and organizational commitment - Sustiyatik, Enni (Faculty of Economics and Business, University of Muhammadiyah Malang, 2023)
This research delves into the connection between transformational leadership, organizational commitment, and lecturer performance within the realm of higher education. Its primary objective is to comprehend how transformational leadership and organizational commitment influence lecturers and their overall effectiveness. The study encompassed 178 lecturers from Kadiri University. Data collection involved the administration of a well-structured questionnaire, and subsequent analysis was conducted using multiple linear regression techniques. The results underscore a robust and positive association between transformational leadership and lecturer performance. Furthermore, the role of organizational commitment in lecturer performance is noteworthy. These findings hold pragmatic significance for educational institutions, highlighting the imperative of cultivating transformational leadership and organizational commitment to augment faculty performance and cultivate dynamic learning environments.